'Green' biocompatible organic–inorganic hybrid electrospun nanofibers for potential biomedical applications. (February 2015) - Manjumeena, R; Elakkiya, T; Duraibabu, D; Feroze Ahamed, A; Kalaichelvan, PT; Venkatesan, R
Gold nanoparticles were prepared by green route using Couroupita guianensis leaves extract. The green synthesized gold nanoparticles exhibited maximum absorbance at 526 nm in the ultraviolet spectrum. By incorporating the green synthesized gold nanoparticles in poly(vinyl alcohol) matrix, unique green organic–inorganic hybrid nanofibers (poly (vinyl alcohol )–gold nanoparticles) were developed by electrospinning. Contact angle measurements showed that the prepared poly (vinyl alcohol)–gold nanoparticles were found to be highly hydrophilic. The crystallinity of gold nanoparticles was analyzed using XRD. The synthesized gold nanoparticles and poly (vinyl alcohol)–gold nanoparticles were characterized using high-resolution transmission electron microscope, Fourier transform-infrared spectroscopy and energy-dispersive analysis of X-ray. The ultimate aim of the present work is to achieve optimum antibacterial, antifungal, biocompatibility and antiproliferative activities at a very low loading of gold nanoparticles. Vero cell lines showed a maximum of 90% cell viability on incubation with the prepared poly (vinyl alcohol)–gold nanoparticles. MCF 7 and HeLa cell lines proliferated only to 8% and 9%, respectively, on incubation with the poly (vinyl alcohol)–gold nanoparticles, and also exhibited good antibacterial and antifungal activities against test pathogenic bacterial and fungal strains. Thus, the poly (vinyl alcohol)–gold nanoparticles could be used for dual applications such as antimicrobial, anticancer treatment besides being highly biocompatible.